2021
DOI: 10.1002/fsn3.2459
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Salidroside on hypoxia‐related liver oxidative stress and inflammation via Nrf2 and JAK2/STAT3 signaling pathways

Abstract: Liver is considered as the largest metabolic organ and functions as the center of numerous metabolic and physiological processes, which plays a pivotal role in high-altitude adaptation (Nath & Szabo, 2012). Liver function disorder may induce maladaption to high altitude and increase the incidence of acute mountain sickness (AMS) (Luks & Swenson, 2015). Although the molecular mechanisms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 44 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…Cytokines bind to receptors, resulting in receptor-coupled JAK aggregation and the activation of adjacent JAKs through mutual phosphorylation. The activated JAKs phosphorylate the tyrosine site on the receptor, causing the receptor to generate a STAT binding region and then phosphorylate STATs ( O'Shea et al, 2015 ; Johnson et al, 2018 ; Xiong et al, 2021 ). In a septic mouse model, blocking the JAK2/STAT3 signaling pathway significantly reduced the levels of HMGB1 and key cytokines and alleviated multi-organ injury ( Hui et al, 2009 ; Xin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines bind to receptors, resulting in receptor-coupled JAK aggregation and the activation of adjacent JAKs through mutual phosphorylation. The activated JAKs phosphorylate the tyrosine site on the receptor, causing the receptor to generate a STAT binding region and then phosphorylate STATs ( O'Shea et al, 2015 ; Johnson et al, 2018 ; Xiong et al, 2021 ). In a septic mouse model, blocking the JAK2/STAT3 signaling pathway significantly reduced the levels of HMGB1 and key cytokines and alleviated multi-organ injury ( Hui et al, 2009 ; Xin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines play a crucial part in inflammatory reactions and tissue injuries or repairs [86–89] . Studies have indicated that SDS could obviously inhibit the expression of inflammatory cytokines in T2D, CCl 4 , furan, hypoxia, HFHC diet and HFD‐induced liver damage [36,90–93] . The NLRP3 inflammasome participates in the generation of mature IL‐1β and evokes inflammatory reaction.…”
Section: Protective Effect Of Sds On Nafld/nashmentioning
confidence: 99%
“…[86][87][88][89] Studies have indicated that SDS could obviously inhibit the expression of inflammatory cytokines in T2D, CCl 4 , furan, hypoxia, HFHC diet and HFD-induced liver damage. [36,[90][91][92][93] The NLRP3 inflammasome participates in the generation of mature IL-1β and evokes inflammatory reaction. Recently, NLRP3 inflammasome has been proven to perform a significant part in the development of NAFLD/NASH.…”
Section: Regulating Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether this improvement can be extended under IR conditions and its underlying mechanism remains unclear. Recently, Rhodiola was found to be a Nuclear factor erythroid 2-related factor 2 (Nrf2) activator, which enhances the antioxidant system to exert neuroprotective effects 19 or relieve hypoxia-induced liver injury 20 . Thus, we hypothesize that Rhodiola activates Nrf2 and the downstream antioxidant system to regulate mitochondrial dynamic homeostasis, finally strengthening cardiac anti-stress capacity under IR conditions.…”
Section: Introductionmentioning
confidence: 99%